Community Empowerment Program for Business Actors Affected by Natural and Non-Natural Disasters in Palu City - Roslinawati Roslinawati; Pricylia Chintya Dewi Buntuang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the empowerment of business communities affected by natural and non-natural disasters in Palu City. This study used a quantitative approach. The population of this study was business actors affected by natural and non-natural disasters in Palu City. The population of this study was 110 business actors. The sample was determined using the census technique. Thus, the entire population was involved as samples. Data were collected by observation, questionnaires, and documentation. Data were analyzed statistically using a t-test. The results of this study indicate that there are differences in community empowerment of business actors affected by natural and non-natural disasters in Palu City. The differences are caused by the different responses to natural and non-natural disasters as the characteristics of disasters are indeed different so the treatment is also different. Based on the results of this study, knowledge, and skills are needed in facing a natural disaster, while the ability to evaluate is more important during the non-natural disaster condition.